KONSEP ALQURAN TENTANG PENDIDIKAN ANAK - Muzakkir Muzakkir (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2016)
The main problem in this articles is how alqur’an concept about child education. Alquran is a guidance in every mankind activities, including education. Alquran has given a direction about child education. Child is a gift of God. Child is the most important assets for every family which must be cared, maintained and educated and Alquran has guided about how to educate child. In Alquran, it is found many concepts about education, even the goals, methods, and the content of its education itself.